(untitled) (Acta Scientiarum. Health Sciences, 2025)
Cannabis sativa has gained notoriety regarding its medicinal applicability. The free-of-charge offer of products containing cannabinoids in the state of São Paulo (Brazil) emerges as a significant milestone in Brazil’s public health history. Although other Brazilian states have not yet foreseen the provision through the Brazilian Public Health System, there is an expectation that they will establish their own respective regulations. An effective national sanitary regulation is crucial to enable the marketing of cannabinoids-containing products with suitable quality, safety and efficacy both the private and public health system. Hence, this review provides a historical analysis of the Brazilian regulations about cannabinoids commercialization, highlighting current regulatory and pharmaceutical development limitations. The commercialization of these products began due to population demand, which led the Brazilian regulatory agency to approve a resolution authorizing the importation of Cannabis-based products. The current national regulatory framework impacts the pharmaceutical development of these products as it limits administration routes and the use of new pharmaceutical technologies. Furthermore, there is also a commercial impact, considering that manufacturers must comply with the requirements of the Pharmaceutical Inspection Cooperation Scheme. Currently, two main resolutions guide the marketing flow of these products in Brazil and further advances are needed to achieve products with quality, efficacy, and safety, which will enable a free public supply to the Brazilian population.